O Efeito de um protocolo de alongamento muscular passivo sobre a cartilagem articular - Renner, Adriana Frias (2005)
Objective: The aim of this study is to evaluate the articular cartilage alterations of rat ankles, after applying unilateral cyclic passive muscle stretching protocol for three weeks in previously immobilized rats. Materials and Methods: Twenty-two male albino rats (280+25.4g) divided into four groups: I-immobilized (n=6), IS-immobilized and stretched (n=5), S-stretched (n=6) and C-control (n=5), were used in this experiment. In the immobilization protocol (groups I and IS) the left ankle joints were immobilized in full plantar flexion and this immobilization device was kept on for four weeks. The animal was allowed free cage activity with the device. In the muscle stretching protocol (groups IS and S) the left ankle joint was manually full dorsal flexed 10 times for 60 seconds with a 30s interval between each 60 second period, seven days a week for four weeks, to stretch the ankle plantar flexors muscle group. At the end of the experiment, the ankles were removed, processed in paraffin, cut and stained with Hematoxilin-Eosin and Safranin-O. Two blinded observers graduated histological and histochemical findings related to cellularity, chondrocyte cloning and Safranin-O staining, observed through light microscopy. For histological and histochemical grading, the Mankin et al (1982) and LeRoux et al (2001) modified grading system was used. For statistical analysis it was used the Spearman test, Kruskal-Wallis nonparametric test with the Post Hoc Newman Keuls and Wilcoxon non-parametric test. Results: The previously immobilized stretching group (treated limbs) presented a significantly higher reduction of proteoglycans content than the solely stretched and solely immobilized groups. No significant effect of muscle stretching on treated limbs concerning cellularity and chondrocyte cloning parameters was detected. Conclusion: These findings suggest that the stretching protocol used was harmful to the previously immobilized articular cartilage. However, the same stretching protocol did not harm the cartilage of non-immobilized groups.